2018
DOI: 10.3390/ijms19061726
|View full text |Cite
|
Sign up to set email alerts
|

Phoenixin—A Pleiotropic Gut-Brain Peptide

Abstract: Phoenixin is a recently discovered brain peptide initially thought to be restricted to reproductive functions. The subsequent identification of phoenixin’s expression in peripheral tissues was accompanied by the description of several other actions of this hormone, such as effects on behavior, sensory perception, memory retention, the cardiovascular system as well as food intake, pointing towards a pleiotropic role of this peptide. The present review will discuss the present knowledge on phoenixin and the sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
(127 reference statements)
0
18
0
Order By: Relevance
“…Moreover, it has also been reported that there is a significant positive correlation of plasma PNX and nesfatin‐1 levels in women affected by polycystic ovarian syndrome (Ullah et al, ). Both PNX (Schalla & Stengel, ) and nesfatin‐1 (Pan, Hsuchou, & Kastin, ) can cross a relatively impermeable blood–brain barrier. Therefore, it is presumed that higher plasma PNX and nesfatin‐1 levels in polycystic ovarian syndrome patients could reach hypothalamus or pituitary cells and affect the GnRH‐dependent HPGA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has also been reported that there is a significant positive correlation of plasma PNX and nesfatin‐1 levels in women affected by polycystic ovarian syndrome (Ullah et al, ). Both PNX (Schalla & Stengel, ) and nesfatin‐1 (Pan, Hsuchou, & Kastin, ) can cross a relatively impermeable blood–brain barrier. Therefore, it is presumed that higher plasma PNX and nesfatin‐1 levels in polycystic ovarian syndrome patients could reach hypothalamus or pituitary cells and affect the GnRH‐dependent HPGA.…”
Section: Discussionmentioning
confidence: 99%
“…Within the hypothalamus, phoenixin and GPR173 are found to be expressed in multiple regions related to reproductive control including the arcuate nucleus (ARC) and anteroventral periventricular nucleus (AVPV). Despite extensive characterization of phoenixin in other peripheral tissues (Prinz et al 2017, Schalla & Stengel 2018, Stein et al 2018, the potential existence of phoenixin and GPR173 in human gonads, and particularly their possible role in human GC regulation has not been discovered yet.…”
Section: Introductionmentioning
confidence: 99%
“…The pleiotropic peptide phoenixin 20 is part of the C4orf52 C-terminus family and is found in a diverse range of species, with few variations. Currently, phoenixin 20 is recognized as having a possible link to a range of bene cial effects, such as reduced anxiety and improved memory, as well as a role in the gut-brain axis [2]. Through its wide-ranging effects and impressive potential to ameliorate various aspects of disease, we identi ed this protein as a possible treatment for atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%